(untitled) (Eurasian Medical Research Periodical, 2025)
This article explains the importance and application of bionic architecture in the climatic conditions of Uzbekistan. The arid and continental climate of Uzbekistan reveals the urgency of saving energy resources, ecological sustainability, and efficient use of natural resources. Recommendations are given that the use of bionic architecture is another direction that is suitable for the environment of Uzbekistan. It is noted that bionic architecture has been widely used in world practice and has achieved good results. The advantages of applying bionics to the architecture of Uzbekistan in the near future are highlighted.